Derived datasets of daily weather, near surface soil status, flow rates and concentrations of nitrogen species from the North Wyke farm platform, EnglandZenodo - Yusheng Zhang; Jane Hawkins; Hadewij Sint; Adrian L. Collins (Data in Brief)
Weather conditions, hydrological responses and the dynamics of key nitrogen species in field runoff were continuously monitored at 15-min resolution on the intensively instrumented North Wyke Farm Platform (NWFP), a UK National Bioscience Research Infrastructure (NBRI), to support research on sustainable and resilient agriculture in the UK. Released data spanning 2013 to 2024 for 6 selected field catchments were aggregated to daily timestep, with reference to data quality flags, to produce continuous weather data, including maximum and minimum air temperature, daily total rainfall, wind speed and quality assured daily average soil moisture content, soil temperature at 15 cm depth, runoff rates, as well as nitrate, nitrite and ammonium concentrations. External data sources were sourced to infill some gaps for the weather data and summary statistics on data coverage were generated for the other data on an annual and seasonal basis where appropriate. Along with detailed field management data, the observed data provide a valuable resource for the parameterisation, calibration and validation of physically-based models for nitrogen losses at field scale to account for alternative management practices and land use under changing climate conditions.